Production and Characterization of Amylase Produced by Raw Starch Degrading Bacteria Using Submerged Liquid Fermentation (SmF) of Agricultural Waste - Nurnikma, Tuah (Universiti Malaysia Sarawak, UNIMAS, 2010)
Amylase is one of the most important enzymes in industrial application. The study investigates the production and the characterization of the amylase that was extracted from raw starch degrading bacteria. D3 isolate is the best amylase producer among three types of bacterial culture. Potato is the best substrate for inducing amylase enzyme production. The result shows the highest production of amylase (2.0179 IU/mL) detected at temperature 37°C after 15 hours incubation period. The best pH for amylase production is pH7 with activity 1.0034 IU/mL as it is the best condition for the bacterial growth. The enzyme was analyzed by using dinitrosalicyclic acid (DNS) assay method. The characterization of enzyme activity was shown the highest activity (0.4698 IU/mL) was produced at temperature 32°C after 20 minutes incubated with 1% soluble starch. The best pH for the enzyme activity is pH5 with 1.3942 IU/mL of reducing sugar detected. The Vmax value of enzyme kinetic study is 0.3429 mg/mL/min and the Km is 1742.4554 mg/mL.